Alternatives measures used by the employees of Hospital Jengka in responding to the job dissatisfaction / Rubina Abd Manaf and Nur Syuhada Nabila Azaman - Abd Manaf, Rubina; Azaman, Nur Syuhada Nabila (2013)
This study is conducted to identify the alternative measures choose by the nurses at Hospital Jengka in responding to the job dissatisfaction. The measures will be based on the concept of EVLN Model from Albert Hirschman which provides the respondents with four choices to be choose which are Exit, Voice, Loyalty and Neglect. This study will help to determine the relationship between employee's behavior toward the job dissatisfaction and the choices they made in responding to the dissatisfaction. The most selected alternative will determine why different employees respond differently. A set of questionnaires will be distributed to the respondents. The respondents will be consisting of 30% of nurses at Hospital Jengka which working at various wards. The data from the questionnaire will be analyzed using Statistical Package for Social Science (SPSS) for Windows.